2023
DOI: 10.3390/ijms24032966
|View full text |Cite
|
Sign up to set email alerts
|

Do Circulating Extracellular Vesicles Strictly Reflect Bronchoalveolar Lavage Extracellular Vesicles in COPD?

Abstract: Cell-derived extracellular vesicles (EVs) found in the circulation and body fluids contain biomolecules that could be used as biomarkers for lung and other diseases. EVs from bronchoalveolar lavage (BAL) might be more informative of lung abnormalities than EVs from blood, where information might be diluted. To compare EVs’ characteristics in BAL and blood in smokers with and without COPD. Same-day BAL and blood samples were obtained in 9 nonsmokers (NS), 11 smokers w/o COPD (S), and 9 with COPD (SCOPD) (FEV1: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…A prior study obtained BAL to compare smokers versus nonsmokers with COPD. 30 In that study, the authors identified differences in macrophage and epithelial-derived EVs between smokers versus nonsmokers with COPD, while no differences were found in EVs collected from plasma. This further supports that utilizing BAL to obtain EVs from the alveolar space more likely represents the complexity of the lung inflammatory response compared with circulating markers.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A prior study obtained BAL to compare smokers versus nonsmokers with COPD. 30 In that study, the authors identified differences in macrophage and epithelial-derived EVs between smokers versus nonsmokers with COPD, while no differences were found in EVs collected from plasma. This further supports that utilizing BAL to obtain EVs from the alveolar space more likely represents the complexity of the lung inflammatory response compared with circulating markers.…”
Section: Discussionmentioning
confidence: 92%
“…To our knowledge, this is the first study to utilize vFC to evaluate surface markers on EVs in the BAL fluid of severely injured patients. A prior study obtained BAL to compare smokers versus nonsmokers with COPD 30 . In that study, the authors identified differences in macrophage and epithelial-derived EVs between smokers versus nonsmokers with COPD, while no differences were found in EVs collected from plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Smokers with COPD showed a significant increase in total CD14 + SOCS3 + EVs when compared with those without COPD and non-smokers. We have previously described that alveolar macrophage-derived (CD14 + ) EVs are increased in COPD patients’ BAL when compared to smokers without COPD ( 30 , 31 ), but the presence of SOCS3 + in macrophage-derived EVs in BAL of COPD patients had not been described before. Importantly, the reported increased counts of CD14 + SOCS3 + EVs in COPD are not only due to the increased of total EVs but also due to the larger percentage of EVs expressing SOCS3 on their surface.…”
Section: Discussionmentioning
confidence: 94%
“…BAL was obtained and immediately processed ( 30 , 31 ) (Group B). According to international guidelines, the BAL collection procedure consisted in positioning the bronchoscope in a wedged position within a bronchial opening.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation